Praktik Perkawinan Janda Tanpa Akta Cerai di Desa Saketa, Kabupaten Halmahera Selatan - Hartono Sabtu; Fatum Abubakar (IAIN Manado, 2023)
The practice of widow marriages without a Divorce Certificate is a phenomenon that often occurs in Saketa Village and is considered commonplace; these marriages are categorized as unregistered marriages at the Office of Religious Affairs, where there are 2 cases and marriages are registered at the Office of Religious Affairs where there is 1 case, but from that the Marriage Law does not permit it. This study aims to practice analyzing widows' marriages without Divorce Certificates in Saketa Village, given Law Number 16 of 2019. The research method used is qualitative; research data comes from primary data, namely data collected directly through observation and interviews with 3 subjects research consisting of 3 widows who married without a Divorce Certificate. The results of this study conclude that the marriage of widows without a divorce certificate in Saketa Village is not by Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. Because the widow's status is not recognized by law, the widow is still the legal wife of her previous husband. Also, because there are no strict sanctions in the Marriage Law against the perpetrators of the intended marriage, these marriages still occur in Saketa Village, West Gane District, South Halmahera Regency. Keywords: Divorce Deed; Widow; Marriage Practices. ABSTRAK Praktik perkawinan janda tanpa Akta Cerai merupakan fenomena yang sering terjadi di Desa Saketa dan sudah dianggap lumrah, perkawinan tersebut dikategorisasi dengan perkawinan tidak terdaftar di Kantor Urusan Agama yang terdapat 2 kasus dan perkawinan terdaftar di Kantor Urusan Agama yang terdapat 1 kasus, namun dari itu tidak dibenarkan oleh Undang-Undang Perkawinan. Penelitian ini bertujuan untuk menganalisis praktik perkawinan janda tanpa Akta Cerai di Desa Saketa dalam pandangan Undang-Undang Nomor 16 tahun 2019. Metode penelitian yang digunakan adalah kualitatif. Data penelitian bersumber dari data primer, yaitu data yang dihimpun secara langsung melalui observasi dan wawancara kepada 3 subjek penelitian yang terdiri dari 3 orang janda yang melakukan perkawinan tanpa Akta Cerai. Hasil penelitian ini menyimpulkan bahwa perkawinan janda tanpa Akta Cerai di Desa Saketa tidak sesuai dengan Undang-Undang Nomor 16 tahun 2019 tentang Perubahan atas Undang-Undang Nomor 1 tahun 1974 tentang Perkawinan. Karena status janda tersebut tidak diakui oleh Undang-Undang, maka janda tersebut masih menjadi istri sah dari suami sebelumnya. Alasan lainnya, tidak ada sanksi yang tegas dalam Undang-Undang perkawinan terhadap pelaku perkawinan yang dimaksud hingga praktik perkawinan tersebut masih terus berlangsung di Desa Saketa, Kecamatan Gane Barat, Kabupaten Halmahera Selatan.